Pengaruh Literasi Zakat, Distribusi Zakat, dan Transparansi Pengelolaan Zakat Terhadap Minat Muzakki di Baznas Deli Serdang - Negara, Raja Fadh Kusuma; Nasution, Yenni Samri Julianti (Multiverse: Open Multidisciplinary Journal, 2024)
This study aims to analyze the influence of zakat literacy, zakat distribution, and transparency in zakat management on the interest of muzakki at BAZNAS Deli Serdang. Zakat, as one of the pillars of Islam, plays a crucial role in promoting income redistribution and alleviating poverty. However, low zakat literacy, suboptimal zakat fund distribution, and lack of transparency are factors that affect the willingness of muzakki to channel their zakat through official institutions. This research employs a quantitative associative approach, with data collected through questionnaires and analyzed using multiple linear regression tests. The results reveal that zakat literacy, zakat distribution, and transparency in zakat management have a positive and significant influence on the interest of muzakki. These findings underscore the importance of professional, transparent, and literacy-based zakat management to enhance public trust and participation, thereby supporting zakat's role as a social and economic instrument.